A variação entre as formas nominais gerúndio e infinitivo gerundivo no português falado em Luanda-Angola: um estudo sociolinguístico - Santos, Abimael Ferreira dos (2022)
With the theoretical-methodological framework of Variationist Sociolinguistics (Labov, 2008[1972]), this dissertation investigated the variation in the use of the gerund and the gerundive infinitive, with oral data from Luanda Portuguese (PL). At first, the present study sought to prove the majority use of the gerundive infinitive in Portuguese spoken in Luanda-Angola, the main hypothesis of this work. In this sense, the objective was to understand the factors that condition the use of the respective phenomenon. This research is based on some studies already carried out, such as: Maler (1972), Barbosa (1999), Mothé (2007; 2014), Oliveira (2017). From a methodological point of view, the sociolinguistic interviews of the project “In search of the roots of Brazilian Portuguese – Phase III: Morphosyntactic Studies” were used, a project based at the Center for Studies in Portuguese Language at the State University of Feira de Santana. In order to comply with the above, 24 informants from the aforementioned project were selected and the data were quantitatively analyzed in real time for a short period with the help of GoldVarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005). In the present research, the results show that there is a more frequent use of the gerundive infinitive among the interviewed speakers, that is, the auxiliary verb + preposition a + infinitive is widely used, and is favored mainly by the factors: verbal structure, type of prayer and schooling. From these results, it is verified the frequent use of the gerundive infinitive in Luanda, a fact that corresponds to a linguistic convergence to European Portuguese (EP), contrary to what occurs in Brazilian Portuguese (BP), which makes a categorical use of the gerúndio, according to research already carried out, such as Barbosa (1999) and Mothé (2014). In this sense, seeking to contribute to the studies on the formation of the sociolinguistic reality of Luanda, it is believed that it is important to carry out studies that focus on data collected in other continents than just the European one - as proposed by Petter (2007) -, because, in this way, it becomes possible to compare the Brazilian variety and the African varieties of Portuguese, expanding the debate on the influence of linguistic contact in the formation of these varieties and the discussion on the role of linguistic and sociocultural factors in linguistic phenomena variables.